MERTI SENDANG, MEMULIAKAN SUMBER AIR DENGAN PENDEKATAN KEBUDAYAAN - Raharjo, Pamuji (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This research aims to look at traditional practices that are still part of the culture of the people of Bleberan Village in Gunungkidul Regency. The existence of the "Kedung Poh" spring cannot be separated from the life of the community. To maintain the existence of the spring, the community carries out the traditional "merti spring" ceremony. The "merti spring" ceremony is a tribute to God Almighty, who has provided a source of water for the community. The method used in this research uses qualitative research methods. Data collection was carried out using interview and observation techniques. The resource persons in this research consisted of community members and community leaders in the Bleberan Village area, "Kedung Poh" spring is in the Bleberan Village area, Kapanewon Playen, Gunungkidul Regency. The results of this research show that the residents of Bleberan Village, with various dynamics of social life, always carry out "merti spring" as a form of gratitude to God Almighty for the existence of the Kedung Poh spring. The "merti spring" ceremony is an important part of maintaining the existence of the spring which has been a source of water to fulfill the water needs of the community.